Price and Quality Competition in Spatial Markets. The Case of Camping Sites - Dieter Pennerstorfer (Austrian Institute of Economic Research (WIFO), 2014)
This paper investigates the influence of competition on price and product quality among Austrian camping sites, a market charactised by both horizontal (spatial) and vertical product differentiation. Theoretically, the effect of competition on quality is ambiguous and depends on the degree of cost substitutability between output and quality. Estimating a system of equations shows that intense competition has a positive impact on product quality and a negative effect on prices (conditional on quality). As high quality is associated with high prices, the total effect of competition on prices is quite small.
Keywords: 330; Spatial competition; price and quality competition; retail markets; camping sites; Ferienunterkunft; Preiswettbewerb; Nichtpreiswettbewerb; Österreich